Cholula durante el siglo XVI: la familia Chimaltecuhtli-Casco - Ruz Barrio, Miguel Ángel (Revista Española de Antropología Americana, 2008)
In this paper, let’s sense beforehand the information that contains the Legajo Chimaltecuhtli-Casco in relation with what it has corresponded itself on Cholula’s history during the beginnings of the colonial epoch. In addition, we centre on presenting to the family Chimaltecuhtli-Casco to that there refers great part of the documentation of this documentary corpus. It is a question of a documentary unpublished corpus up to the moment, since it’s in a collection deprived of USA, which it includes from 1561 to 1660. In addition, in there appears a variety of situations that reflect different aspects of what was happening in this place during this period, since there appear different lawsuits, testaments and sales of lands.